Specific activation of the cellular Harvey-ras oncogene in dimethylbenzanthracene-induced mouse mammary tumors. - Dandekar, S (1986)
Genomic DNAs from dimethylbenzanthracene-induced BALB/c mouse mammary tumors arising from the transplantable hyperplastic outgrowth (HPO) line designated DI/UCD transformed NIH 3T3 cells upon transfection. Transforming activity was attributed to the presence of activated Harvey ras-1 oncogenes containing an A----T transversion at the middle adenosine nucleotide in codon 61. DNAs from untreated DI/UCD HPO cells and radiation-induced and spontaneous mammary tumors from the DI/UCD HPO line failed to transform NIH 3T3 cells. The results indicated that the mutation activation of Harvey ras-1 oncogenes was specific to dimethylbenzanthracene treatment in the mouse mammary tumor system.